Ethical aspects of prenatal screening and diagnosis. - Da Graça, L M (Acta Médica Portuguesa, 1992)
The general principles of the European Council's draft Recommendation on Prenatal Screening and Diagnosis are presented. Those principles include the conditions for performing prenatal tests, the need for previous genetic counselling, and for fully informed consent, and the ethical rules for the use of individual data gathered.